2010
DOI: 10.1111/j.1365-2427.2010.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of the feedback of phytoplankton on thermal structure via light extinction

Abstract: Summary 1. A simulation study of the feedback of phytoplankton biomass on temperature stratification in the large, monomictic Lake Constance was undertaken. Phytoplankton biomass affects the light extinction coefficient (LEC) of the water and, in turn, the vertical distribution of short‐wave radiation, which shapes the temperature stratification in the lake. 2. A sensitivity study of the variation in LEC using the hydrodynamic model DYRESM showed that a high LEC is associated with stronger stratification, shal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 48 publications
(97 reference statements)
8
68
0
Order By: Relevance
“…It was also shown that the model is very sensitive to variations in K d when the value is less than 0.5 m −1 . This finding is in agreement with the study of Rinke et al (2010) and the recent study of Heiskanen et al (2015) who determined that the impact of seasonal variations of K d on the simulated thermal structure is small, for a lake with K d values larger than 0.5 m −1 . The studies suggested that the response of 1-D lake models to K d variations is nonlinear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was also shown that the model is very sensitive to variations in K d when the value is less than 0.5 m −1 . This finding is in agreement with the study of Rinke et al (2010) and the recent study of Heiskanen et al (2015) who determined that the impact of seasonal variations of K d on the simulated thermal structure is small, for a lake with K d values larger than 0.5 m −1 . The studies suggested that the response of 1-D lake models to K d variations is nonlinear.…”
Section: Discussionsupporting
confidence: 93%
“…However, the sensitivity increased rapidly for K d values less than our Min (0.58 m −1 ). This result supported the study of Rinke et al (2010) that the thermal structure of lakes is particularly sensitive to changes in K d when its value is below 0.5 m −1 . More recently, Heiskanen et al (2015) confirmed the critical threshold of K d (ca.…”
Section: Sensitivity Of Flake To K D Variationssupporting
confidence: 88%
“…Remaining phytoplankton were separated by size, forming 'small' and 'large' algal groups, given the importance of size in determining light and light utilization traits, among others (Finkel et al, 2010). There exist modelling studies where taxonomic classes were parameterized directly as functional groups (e.g., Jöhnk et al, 2008;Carraro et al, 2012), but categorization based on size, thereby combining di erent taxonomic classes within a given functional group like in this study is not uncommon (e.g., Mieleitner and Reichert, 2008;Gal et al, 2009;Rinke et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…From the point of view of atmospheric feedbacks, ecosystem function is more than just ontologically relevant and is a controlling factor for heat exchange. Previous studies illustrate the feedback between phytoplankton and thermal structure, via light extinction modulation (Tilzer, 1983(Tilzer, , 1988Mazumder et al, 1990;Rinke et al, 2010). Thermal stratification modulates oxygen concentrations and therefore ecosystem function (Elçi, 2008).…”
Section: Introductionmentioning
confidence: 97%